2015
DOI: 10.1002/acr.22470
|View full text |Cite
|
Sign up to set email alerts
|

Risks of Herpes Zoster in Patients With Rheumatoid Arthritis According to Biologic Disease‐Modifying Therapy

Abstract: Objective To evaluate whether the risks of herpes zoster (HZ) differed by biologic agents with different mechanisms of action (MOAs) in older rheumatoid arthritis (RA) patients. Methods Using Medicare data from 2006–2011, among RA patients with prior biologic agent use and no history of cancer or other autoimmune diseases, this retrospective cohort study identified new treatment episodes of abatacept, adalimumab, certolizumab, etanercept, golimumab, infliximab, rituximab, and tocilizumab. Followup started on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
77
4
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(95 citation statements)
references
References 18 publications
8
77
4
4
Order By: Relevance
“…There was no difference in the risk of HZ between patients in group 2 (hazard ratio [HR] 1.34, 95% confidence interval [95% CI] 1.13-1.59) and group 3 (HR 1.38, 95% CI 1.08-1.77). Among TNF antagonists, we found a lower risk for HZ with the use of etanercept (HR 0.62, 95% CI 0.40-0.95) and adalimumab (HR 0.53, 95% CI 0.31-0.91) compared to infliximab, similar to findings by Galloway et al (4), but in contrast to those from the German biologics registry RABBIT (Rheumatoid Arthritis Observation of Biologic Therapy) (4) and the current study by Yun et al (1). One common and important risk factor for HZ in RA that emerged from all these studies was glucocorticoid use.…”
Section: To the Editorcontrasting
confidence: 57%
See 2 more Smart Citations
“…There was no difference in the risk of HZ between patients in group 2 (hazard ratio [HR] 1.34, 95% confidence interval [95% CI] 1.13-1.59) and group 3 (HR 1.38, 95% CI 1.08-1.77). Among TNF antagonists, we found a lower risk for HZ with the use of etanercept (HR 0.62, 95% CI 0.40-0.95) and adalimumab (HR 0.53, 95% CI 0.31-0.91) compared to infliximab, similar to findings by Galloway et al (4), but in contrast to those from the German biologics registry RABBIT (Rheumatoid Arthritis Observation of Biologic Therapy) (4) and the current study by Yun et al (1). One common and important risk factor for HZ in RA that emerged from all these studies was glucocorticoid use.…”
Section: To the Editorcontrasting
confidence: 57%
“…The study by Yun et al (1) in a recent issue of Arthritis Care & Research examining the risk of herpes zoster (HZ) in patients with rheumatoid arthritis (RA) initiated on biologic disease-modifying antirheumatic drugs revealed that the incidence of HZ was similar among the patient groups treated with the different biologic agents, which included the 5 anti-tumor necrosis factor (anti-TNF) agents, abatacept, rituximab, and tocilizumab.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Event types such as malignancies or opportunistic infections did not emerge with prolonged treatment. Herpes zoster infections were reported without evidence of a dose effect during the OLE period at incidence rates (2.3/100 patient-yrs) similar to those described in association with biologic DMARD in RA 7,8 . Laboratory abnormalities leading to discontinuation were uncommon.…”
Section: Discussionmentioning
confidence: 69%
“…We considered that the relationship between HZ and biologics was significant when the HZ events occurred during the biologic treatment or within the recommended dosing intervals after the discontinuance of biologics. The recommended dosing intervals were defined as follows: 30 days for abatacept, golimumab, and tocilizumab; 56 days for infliximab; and 180 days for rituximab [16].…”
Section: Hz Verificationmentioning
confidence: 99%